2015
DOI: 10.1016/j.jhep.2014.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life after liver donation in the adult to adult living donor liver transplantation cohort study (A2ALL)

Abstract: Background and Aims. There are few long-term studies of health-related quality of life (HRQOL) in living liver donors. This study aimed to characterize donor HRQOL in the Adult to Adult Living Donor Liver Transplantation Study (A2ALL) up to 11 years post-donation. Methods. Between 2004-2013, HRQOL was assessed at evaluation, and 3 months and yearly post-donation in prevalent liver donors using the Short Form survey (SF-36), which provides a physical (PCS) and a mental component summary (MCS). Results. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 52 publications
7
91
1
1
Order By: Relevance
“…The articles were Updates in Psychosomatic Medicine related to 15 subspecialties: cardiac psychiatry, [4][5][6][7][8][9] collaborative care/integrated behavioral health, 10,11 emergency psychiatry, 12,13 HIV psychiatry, [14][15][16][17][18][19][20] neuropsychiatry, 21-31 pediatric psychosomatic medicine, 32-36 psychodermatology, [37][38][39][40][41][42][43][44][45] psychonephrology, 46-55 psycho-oncology and palliative care, [56][57][58][59][60][61][62][63][64] serious mental illness, [65][66][67][68][69][70][71][72] somatic symptom disorders, 73 suicide, 74-78 transplant psychiatry, [79][80][81][82][83][84]…”
Section: Resultsmentioning
confidence: 99%
“…The articles were Updates in Psychosomatic Medicine related to 15 subspecialties: cardiac psychiatry, [4][5][6][7][8][9] collaborative care/integrated behavioral health, 10,11 emergency psychiatry, 12,13 HIV psychiatry, [14][15][16][17][18][19][20] neuropsychiatry, 21-31 pediatric psychosomatic medicine, 32-36 psychodermatology, [37][38][39][40][41][42][43][44][45] psychonephrology, 46-55 psycho-oncology and palliative care, [56][57][58][59][60][61][62][63][64] serious mental illness, [65][66][67][68][69][70][71][72] somatic symptom disorders, 73 suicide, 74-78 transplant psychiatry, [79][80][81][82][83][84]…”
Section: Resultsmentioning
confidence: 99%
“…Clinical conditions that virtually sealed the death prognosis currently have new therapeutic approaches that ensure longer survival and resolution of various conditions of extreme severity. For example, in end-stage liver failure, a severe medical condition that usually affects patients with chronic or acute liver disease, as in acute fulminant hepatitis (1) , liver transplantation became a therapeutic alternative of great effectiveness, affecting survival and improving quality of life (2) . To enable the care of these worsening health conditions, hospitals have undergone major transformations in their physical infrastructure and in personnel qualification.…”
Section: Introductionmentioning
confidence: 99%
“…To enable the care of these worsening health conditions, hospitals have undergone major transformations in their physical infrastructure and in personnel qualification. The management of end-stage liver failure demands the development of specific skills from the care staff, from both the medical-surgical point of view and the nursing process (2) , and requires the availability of therapeutic resources, technical and administrative support. Issues related to the existence of appropriate technologies, maintaining low risk contamination environments and the development of logistics processes for selection and collection of organ and tissue started to dominate the routine of specialized units' managers (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of LDLT have shown acceptable results in terms of short-term survival and graft outcomes compared with deceased donor liver transplantation with full size organ (1) and long-term donor quality of life (2). In the nine-center adult-to-adult living donor liver transplantation cohort study (A2ALL), one-year graft survival was 81% (3) and most living donors maintained an above average health-related quality of life at 11 years postoperatively (4). In addition, recent advancements in surgical techniques and presurgical evaluation and preparation have continued to improve outcomes (5).…”
mentioning
confidence: 99%